Hepatitis E virus open reading frame 3 protein interacts with porcine liver‐specific plasminogen and α2‐antiplasmin. Issue 3 (19th November 2013) - Zhou, Yan; Geng, Yansheng; Yang, Jun; Zhao, Chenyan; Harrison, Tim J.; Wang, Youchun
Abstract Hepatitis E virus (HEV) is a hepatotropic virus that causes acute and, occasionally, chronic viral hepatitis. At least four recognized genotypes of mammalian HEV have been identified. Genotypes 3 and 4 are zoonotic in humans and pigs are the major host. The 7.2 kb genome of HEV contains three open reading frames: ORF1, ORF2, and ORF3. ORF1 encodes a nonstructural protein and the ORF2 protein is the main capsid protein but the precise functions of ORF3 protein remain obscure. To explore the role of ORF3 in the porcine host, the genotype 4 ORF3 protein was used for yeast two‐hybrid screening to find cellular binding partners encoded by a pig liver cDNA library, two porcine liver specific proteins, plasminogen and α2‐antiplasmin were identified. Their interactions with the ORF3 protein were validated by chemiluminescent Co‐Immunoprecipitation assay and by Western blotting in Co‐IP and His pull‐down assay. The biological significance of these interactions and their possible role in the HEV infection are discussed. J. Med. Virol. 86:487–495, 2014. © 2013 Wiley Periodicals, Inc.